Tinjauan Hukum Islam Terhadap Praktik Bagi Hasil Tangkapan Ikan Nelayan di Desa Kedungrejo Kecamatan Muncar Kabupaten Banyuwangi - Haq, Azriadian El; , Dr. Muh. Muinudinillah Basri, MA (2016)
Mudarabah is one of Islamic concepts in making agreement of profit-sharing in which a party provides capital (sahibul mall) and the other one (mudorib) operates the capital. The concept has been used since long time ago and it has been also adopted by Islam followers. Purpose of the research is to know how does Islamic law review on fish-sharing practice among fishermen in Kedungrejo village, Kecamatan Muncar, Banyuwangi Regency. The final task discusses aspects of agreement and legal consequence, fish-sharing procedure, fish-sharing method and its accordance with Islamic law. Data was collected by using observation, interview and documentation methods. After data analysis by using descriptive-qualitative analysis, it was known that fish-sharing practiced by fishermen of Kedungrejo village for awitan, gardan and slerek boats was in accordance with Islamic rules and requirements. Awitan boat used five division system, namely 2 portions for boat owner, 2 portions for pandhega and 1 portion for boat keeper. In addition, fishermen also had rights for lawuhan. Gardan boat used fifty-fifty system and lawuhan that were divided after landing. Slerek boat practiced monthly produces (fifty-fifty) and bon-bonan, daily fish-sharing, namely pakek laut, pacokan, bagi rosak and pocket money. Such production-sharing does not contradict with Islamic law because fifty-fifty sharing had been practiced by Prophet Muhammad. Similarly, pakek laut, pacokan, lawuhan and pocket money that can be included in category of additional profit requirements in Islamic law was not causing the breaking of agreement. Bagi rosak can be categorized in tabarru' (voluntary contribution). Meanwhile, bon-bonan system can be subjected to fasid requirements, but mudarabah agreement is still valid. Keywords: Mudarabah, Islamic Law, Fishermen, Fish-sharing, Kedungrejo